PIBID Subprojeto Alfabetização Cartográfica e formação de professores em Geografia na Unimontes - Carvalho, Pedro Henrique Maia de (2020)
Although the progress of the Brazilian basic school in public education is noticeable, there is still a precariousness of education in Brazil. The educational sector is considered one of the most important spheres for the development of a country. It is important to note that Brazil in the education sector has done a lot with the introduction of programs that aim at good quality education. Thus, in this work, the program created by the federal government, the Institutional Program for Teaching Initiation Grants (PIBID), is portrayed, showing the Cartographic Literacy Subproject of the State University of Montes Claros (Unimontes), which aims to qualify in teacher training and School Cartography. With the interventions carried out at the educational institution that hosted this subproject, it was possible to bring academics to learn about the reality of teaching at a public school in the city of Montes Claros, in the north of Minas Gerais. This Subproject lasted from 2014 to 2018, an opportune time to develop teaching practices that enabled academics to put into practice the contents learned in the academy, the application of playful practices and the promotion of the training of reflective teachers and researchers. Therefore, the objective of this work is to analyze the formation of teachers in Geography, through PIBID Cartographic Literacy Subproject - Unimontes, from March 2014 to March 2018. The methodology used to elaborate the work was initially a bibliographic reference research for to better understand about teacher education, PIBID as public policy and School Cartography, we use the narrative methodology to collect the data of the work that consisted of reports from 16 ex-Pibidians who participated in this Subproject, in addition to photographic records of the activities developed and documentary research to understand the formation of this program. We concluded that the PIBID Cartographic Literacy Subproject collaborated in the formation of teachers in Geography, making them more qualified professionals to teach Cartography to schoolchildren and encouraged them to pursue a teaching career.